Pengaruh Green Accounting dan Good Governance Terhadap Kinerja Keuangan Dengan Corporate Social Responsibility Sebagai Variabel Moderasi: Studi Empiris pada Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2022-2024 - Sri Wahyuni; Andy Dwi Bayu Bawono (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Financial performance is the main indicator for evaluating a company's effectiveness and efficiency. This study aims to analyze the effect of environmental cost accounting, environmental information disclosure, independent commissioners, and institutional ownership on financial performance, with corporate social responsibility as a moderating variable. The population in this study was all companies listed on the Indonesia Stock Exchange in 2022-2024. The sampling technique used a purposive sampling method and obtained a sample of 57 non-cyclical consumer companies listed on the Indonesia Stock Exchange and meeting the criteria. Financial performance was measured using Return on Assets (ROA). The research method used was quantitative research. The data sources in this study used secondary data in the form of annual financial reports and company sustainability reports. The data analysis technique used was multiple linear regression analysis with the SPSS 27 program. The results showed that institutional ownership variables affected financial performance, while environmental cost accounting, environmental information disclosure, and independent commissioners did not affect financial performance. Furthermore, corporate social responsibility was unable to strengthen or weaken the relationship between all independent variables and the dependent variable.